UJI AKURASI PIRANTI SENSOR TRANSDUSER UNTUK MENENTUKAN WAKTU TERJADINYA BERAHI PADA SAPI - Suyadi Suyadi; Kuswati Kuswati; B. Susilo; J. A. E. Noor (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2010)
The success of estrus detection ensure the correct time of insemination so the high conception rate can be resulted. This research was objected to design an electronic equipment as sensor transducer for measuring the change of circular pressure of vaginal wall of the cows. A sensor used was Load cell type M322. The sensor was connected to microcontroller and a display. The results showed that the applied sensor on a stainless steel transducer steak with a diameter of 2.5 cm and length of 40 cm measured a sensitive change of pressure attach it. This sensitivity was tested to measure the change of pressure of different dept of water i.e. 0, 10, 20, 30, 40 and 50 cm. Two equations was resulted from this measurement, while a linear regression was Y= -36.412+197.53X a quadratic equation was Y= 253.3+84.09X+5.09X2. The sensor was then applied in estrus beef cow, not estrus beef cow and estrus dairy cow for 10 days. The same pattern was observed in estrus of both beef and dairy cows: a high values were detected in the non estrus phase while during estrus phase the values were in basal. In contrast, anestrus cow showed high value during 10 days observation, and 5 min application of each. In conclusion, this designed estrus detector was possible to be developed toward application in the farmers after some modifications were created. (JIIPB 2010 Vol 20 No 1: 11-21). Key words : sensor transducer, uterine wall pressure, estrus-non estrus cows